2003
DOI: 10.1097/01.ccm.0000098031.24329.10
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adequate empirical antibiotic therapy on the outcome of patients admitted to the intensive care unit with sepsis*

Abstract: In patients admitted to the ICU for sepsis, the adequacy of initial empirical antimicrobial treatment is crucial in terms of outcome, although early mortality rate was unaffected by the appropriateness of empirical antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
338
6
15

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 642 publications
(381 citation statements)
references
References 44 publications
15
338
6
15
Order By: Relevance
“…If an infectious cause of fever is suspected, empirical antimicrobial therapy is urgent. Indeed, delaying effective antimicrobial therapy has been associated with increased mortality [49,[110][111][112][113][114]. Barie and associates [115] demonstrated in a prospective observational study that the delayed-antibiotic therapy increased the risk of death by 2.1% for every 30 minutes' delay (OR, 1.021; 95% CI, 1.003 to 1.038).…”
Section: 47 For Healthcare-associated Infections Non-responsive To mentioning
confidence: 99%
See 1 more Smart Citation
“…If an infectious cause of fever is suspected, empirical antimicrobial therapy is urgent. Indeed, delaying effective antimicrobial therapy has been associated with increased mortality [49,[110][111][112][113][114]. Barie and associates [115] demonstrated in a prospective observational study that the delayed-antibiotic therapy increased the risk of death by 2.1% for every 30 minutes' delay (OR, 1.021; 95% CI, 1.003 to 1.038).…”
Section: 47 For Healthcare-associated Infections Non-responsive To mentioning
confidence: 99%
“…The initial selection of antimicrobial therapy should be broad enough to cover all likely pathogens [110][111][112]115,117,118]. Kollef et al showed [117] that the prior administration of antibiotics (implying an increased risk of resistant pathogens) and the presence of a bloodstream infection (especially catheter-related: implying resistant gram positive cocci and failure to treat fungemia empirically) were the main causes of inappropriate therapy and increased mortality.…”
Section: 47 For Healthcare-associated Infections Non-responsive To mentioning
confidence: 99%
“…Only 63% of 3413 subjects received an antibiotic active against the infecting pathogen, and their mortality was 20%, 14% lower than that in the group that received ineffective antibiotics (P ϭ .0001). 25 Other authors have reported even worse outcomes with ineffective therapy: 62% mortality among inadequately treated bacteremic or fungemic ICU patients, compared with 28.4% among those who were adequately treated 26 and an odds ratio of dying of 8.14 for the 46 of 270 septic ICU patients who received inadequate initial antibiotics, 27 making inadequate antibiotic therapy the strongest risk factor for death. Finally, Kollef et al reported that 26% of 655 infected ICU patients received inadequate antibiotics and suffered an infection-related mortality rate of 40.2%, more than twice the 17.7% rate among adequately treated patients (P Ͻ .001).…”
Section: Early Effective Antibioticsmentioning
confidence: 99%
“…74 Figure 3 compares the corresponding NNT values to save 1 life; according to the available data, a hospitalist is 5-8 times more likely to save a life with EGDT than with fibrinolysis. Because the literature supporting several major sepsis therapies have been limited to retrospective studies [18][19][20][21][22][23][24][25][26][27][28] and single randomized, controlled trials 29,36 and because key trials are still underway (CORTICUS, NICE-SUGAR), the benefits of sepsis therapies are less certain than are those for the treatment of MI. This was underscored by the finding that the benefit in reduced mortality of intensive insulin in the surgical ICU 57 did not extend to all patients in the medical ICU.…”
Section: Conclusion: Deadly Yet Treatablementioning
confidence: 99%
“…Sepsis accounts for approximately 60,000 fatalities annually and is the third most common cause of death in Germany [2]. Timely commencement of an appropriate antibiotic treatment is directly related to survival rate [3,4,5,6]. Rapid and reliable detection of the causative agent is therefore crucial to optimizing treatment and improving survival rates.…”
Section: Introductionmentioning
confidence: 99%